Launching A Weaning Food in a Developing Country - Amine, Lyn S. (2016)
Discusses the various stages in the launch of a new weaning food in Morocco. Highlights inherent problems in marketing a product in Morocco, including government inefficiencies and weaknesses in the retailing infrastructure. Examines the need for a new weaning food in the country due to high levels of malnutrition. Describes the launch of the mew product by the World Health organization and the US Agency for International Development. Discusses the products failure and analyses reasons for this failure including: The Moroccan market environment; The pricing strategy; The distribution strategy; Conflicting aims of the government and the individual entrepreneur. Examines lessons to be learnt from the failure, and techniques to be used in the future including: The conduct of a detailed marketing strategy by an advertising agency. The creation of a focused distribution strategy. Enhance support from the Moroccan government. Concludes that the success of a product in a country like Morocco will depend upon the quality of future marketing planning, and the programme implementation and follow‐up, in addition to the personal commitment of those carrying out the new venture.